EFEKTIVITAS TEKNIK MIND MAPPING UNTUK MENINGKATAN KEMAMPUAN MENGENAL HURUF BAGI ANAK TUNDAKSA - Sahari Almaini (Jurnal Penelitian Pendidikan Khusus, 2015)
This research motivated by the findings at SLB Fan Redha Padang. About children with physical disabilities X are not familiar with consonants. Researchers want to improve the ability to know bilabial consonants (b, p and m). Researchers want to improve the ability to know bilabial consonants (b, p and m) were presented at the beginning, middle and end of words with mind mapping technique. The aim of research to prove whether the min mapping technique effective to improve recognize letters. The research approach A-B-A single subject research design and data analysis techniques using visual analysis graph. Based on the research results, mind mapping is effective techniques to improve the ability to know letters for children with physical disabilities in SLB Fan Redha Padang. Further, the results of this research were expected to be useful for both teachers and the upcoming researcher if similar case was found. Keyword: Anak Tunadaksa, Kemampuan Mengenal Huruf, Teknik Mind Mapping.